Estratégias de marketing de serviços B2B: estudo multicaso em empresas fabricantes de máquinas e equipamentos - Ribeiro, Ricardo Veloso (2017)
Machine manufacturers and operations between the integrated solut ions of products and services that meet the needs of customers. This sector is important for national sustainable economic development. However, there is little academic research on the strategy and management of services performed by these companies, as h ighlighted in the bibliometric analysis performed in the present study. Thus, a gift aims to identify and analys e how B2B services marketing strategy executed by companies manufacturing machines and equipment and alignment with a customer expectation. The Research was developed with 4 multinational companies, leaders in the segment in which they operate, and 9 client companies, with a total participation of 29 professionals that work in the areas of marketing, sales, projects, technical technique, HR, maint enance and production. The research has a qualitative approach and is developed throu gh multiple case studies, analys ing in the field, as a service marketing strategy from the perspective of the machine and equipment manufacturers and from the customer per spective, based on a literature review on Service M arketing And industrial marketing. As a result, a conceptual framework is presented which shows that the relationship can be affected by several elements of service marketing, such as product, distribution , people and price. However, the price of technical service does not affect the relationship, but the price of spare parts has been highlighted by some customers, such as motivation to look for another supplier. It is noted that it is industrial marketing as trust and commitment are also affected by other elements of marketing services such as communication, productivity and quality.